DDT... A deadly new bug killer as potent against insects as the sulfas and penicillin are against disease - Adams, Walter (1944)
Better Homes & Gardens Magazine article describing the history, function, and effects of DDT on pests. Advertises the use of DDT for use in one's garden or home. The article includes a cartoon illustration of a mosquito ingesting DDT and consequently reaching its demise. Better Homes and Gardens a best-selling magazine in the United States founded in 1922 by Edwin Meredith, who had previously been the United States Secretary of Agriculture under Woodrow Wilson. Better Homes and Gardens focuses on interests regarding homes, cooking, gardening, crafts, healthy living, decorating, and entertaining. The original magazine name was Fruit, Garden and Home from 1922 to 1924. The name was changed to Better Homes and Gardens beginning with the August 1924 issue.
Keywords: DDT (Insecticide); Insecticides; Insecticides--Toxicology; Better homes and gardens books; Home economics; Insect pests; Pests--Control; Periodicals